IL-10-Producing B Cells Are Induced Early in HIV-1 Infection and Suppress HIV-1-Specific T Cell Responses - Liu, Jun; Zhan, Wei; Kim, Connie J.; Clayton, Kiera; Zhao, Hanqi; Lee, Erika; Cao, Jin Chao; Ziegler, Blake; Gregor, Alexander; Yue, Feng Yun; Huibner, Sanja; MacParland, Sonya; et al. (PLOS ONE, 2014)
A rare subset of IL-10-producing B cells, named regulatory B cells (Bregs), suppresses adaptive immune responses and inflammation in mice. In this study, we examined the role of IL-10-producing B cells in HIV-1 infection. Compared to uninfected controls, IL-10-producing B cell frequencies were elevated in both blood and sigmoid colon during the early and chronic phase of untreated HIV-1 infection. Ex vivo IL-10-producing B cell frequency in early HIV-1 infection directly correlated with viral load. IL-10-producing B cells from HIV-1 infected individuals were enriched in CD19+TIM-1+ B cells and were enriched for specificity to trimeric HIV-1 envelope protein. Anti-retroviral therapy was associated with reduced IL-10-producing B cell frequencies. Treatment of B cells from healthy donors with microbial metabolites and Toll-like receptor (TLR) agonists could induce an IL-10 producing phenotype, suggesting that the elevated bacterial translocation characteristic of HIV-1 infection may promote IL-10-producing B cell development. Similar to regulatory B cells found in mice, IL-10-producing B cells from HIV-1-infected individuals suppressed HIV-1-specific T cell responses in vitro, and this suppression is IL-10-dependent. Also, ex vivo IL-10-producing B cell frequency inversely correlated with contemporaneous ex vivo HIV-1-specific T cell responses. Our findings show that IL-10-producing B cells are induced early in HIV-1 infection, can be HIV-1 specific, and are able to inhibit effective anti-HIV-1 T cell responses. HIV-1 may dysregulate B cells toward Bregs as an immune evasion strategy.